2017
DOI: 10.3389/fneur.2017.00133
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drugs Impair Shortening of Isolated Cardiomyocytes

Abstract: BackgroundMost antiepileptic drugs (AEDs) inhibit seizure generation by acting on voltage-dependent ion channels. Voltage-dependent sodium and calcium channels are commonly expressed in brain and heart, suggesting that AEDs may have considerable cardiodepressive effects, thereby facilitating sudden cardiac death as a potential cause of sudden unexpected death in epilepsy. Here, we investigated the effects of carbamazepine (CBZ), lamotrigine (LTG), and levetiracetam (LEV) alone and in combination on the shorten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Importantly, at very high doses, after ingestion ("overdose'') or in combination with other sodium channel blocking agents or ASMs at higher daily doses, sodium channel inhibitors were reported to cause cardiac arrhythmias, independently of pre-existing cardiac diseases. The use of carbamazepine, lacosamide, lamotrigine and phenytoin was mostly associated with bradyarrhythmias (such as sinus node dysfunction and AV block), but also with ventricular tachyarrhythmia and atrial fibrillation [126][127][128][129][130][131]. The reports on ASM-induced alterations of cardiac autonomic control and HRV are controversial, but according to a meta-analysis including six original studies, there is no apparent effect of ASM on HRV [132].…”
Section: • 31mentioning
confidence: 99%
“…Importantly, at very high doses, after ingestion ("overdose'') or in combination with other sodium channel blocking agents or ASMs at higher daily doses, sodium channel inhibitors were reported to cause cardiac arrhythmias, independently of pre-existing cardiac diseases. The use of carbamazepine, lacosamide, lamotrigine and phenytoin was mostly associated with bradyarrhythmias (such as sinus node dysfunction and AV block), but also with ventricular tachyarrhythmia and atrial fibrillation [126][127][128][129][130][131]. The reports on ASM-induced alterations of cardiac autonomic control and HRV are controversial, but according to a meta-analysis including six original studies, there is no apparent effect of ASM on HRV [132].…”
Section: • 31mentioning
confidence: 99%
“…For instance, rapid intravenous application of phenytoin and sedatives such as barbiturates, benzodiazepines, and anesthetic agents are known to lower BP or to induce hypotension (94). These acute effects are likely to be induced by inhibition of voltage-gated sodium and calcium channels with subsequent decrease of cardiac contractility and SV [for review see e.g., (95)]. Probably the most common effects of anti-seizure agents on BP are of indirect nature and related to weight gain [e.g., upon intake of valproic acid, gabapentin, and pregabalin (6)] and detrimental effects on circulating cardiovascular risk factors such as dyslipidemia and hyperhomocysteinemia mostly caused by enzyme-inducing anti-seizure drugs (e.g., carbamazepine, phenobarbital, phenytoin) which in turn may lead to atherosclerosis with decreased blood vessel flexibility and reactivity (9698).…”
Section: Interictal Alterations Of Blood Pressure and Baroreflex In Ementioning
confidence: 99%
“…These drugs increase the risk of arrhythmias (proarrhythmic effect) such as ventricular tachycardia and death in individual with structural heart disease and thus should not be use is theses patients [32]. In murine models, Hubert et al found that carbamazepine, lamotrigine and levetiracetam use were associated to a reduction in cardiac myocyte contraction and excitability compromising electromechanical coupling which was more intense with association of drugs [33].…”
Section: Antiepileptic Drugs and Autonomic Functionmentioning
confidence: 99%